Extra‐plastidial degradation of chlorophyll and photosystem I in tobacco leaves involving 'senescence‐associated vacuoles'. (25th May 2019) - Gomez, Facundo M.; Carrión, Cristian A.; Costa, María L.; Desel, Christine; Kieselbach, Thomas; Funk, Christiane; Krupinska, Karin; Guiamet, Juan
Summary: Chlorophyll (Chl) loss is the main visible symptom of senescence in leaves. The initial steps of Chl degradation operate within the chloroplast, but the observation that 'senescence‐associated vacuoles' (SAVs) contain Chl raises the question of whether SAVs might also contribute to Chl breakdown. Previous confocal microscope observations (Martínez et al ., 2008) showed many SAVs containing Chl. Isolated SAVs contained Chl  a and b (with a Chl  a / b ratio close to 5) and lower levels of chlorophyllide  a . Pheophytin  a and pheophorbide  a were formed after the incubation of SAVs at 30°C in darkness, suggesting the presence of Chl‐degrading activities in SAVs. Chl in SAVs was bound to a number of 'green bands'. In the most abundant green band of SAVs, Western blot analysis showed the presence of photosystem I (PSI) Chl‐binding proteins, including the PsaA protein of the PSI reaction center and the apoproteins of the light‐harvesting complexes (Lhca 1–4). This was confirmed by: (i) measurements of 77‐K fluorescence emission spectra showing a single emission peak at around 730 nm in SAVs; (ii) mass spectrometry of the most prominent green band with the slowest electrophoretic mobility; and (iii) immunofluorescence detection of PsaA in SAVs observed through confocal microscopy. Incubation of SAVs at 30°C in darkness caused a steady decrease in PsaA levels. Overall, these results indicate that SAVs may be involved in the degradation of PSI proteins and their associated chlorophylls during the senescence of leaves. Significance Statement: This article reports on the finding of chlorophyll and photosystem‐I proteins in 'senescence‐associated vacuoles', which are likely to be degraded within these vacuoles.